The Basin of Mexico Hydrogeological Database (BMHDB): Implementation, queries and interaction with open source software - Carrera-Hernández, J.J.; Gaskin, S.J. (Environmental modelling & software : with environment data news, 2008)
Integrated Water Management at the Basin level is a concept that was introduced in the 1990s and is a goal in every national and local water management plan. Unfortunately this goal has not been achieved mainly due to a lack of both tools and data management, as data must be gathered from different sources and in different formats. Compounding this problem is the fact that in some regions different water agencies are in charge of water supply as is the case in the Basin of Mexico, in which Mexico City and its Metropolitan Zone are located. The inhabitants of the Basin of Mexico, which comprises five different political entities and in which different agencies are in charge of water supply rely on the Basin's aquifer system as its main water supply source. However, a regional hydrogeological database in this area does not exist which is why the use of both a Relational Database Management System (RDMBS) and a Geographic Information System (GIS) is proposed in order to improve regional data management in the study area. Data stored in this new database, the Basin of Mexico Hydrogeological Database (BMHDB) comprise data on climatological, borehole and run-off variables, readily providing information for the development of hydrogeological models. A simple example is used to show how geostatistical analysis can be done using the data directly from the BMHDB. The structure of the BMHDB allows easy maintenance and updating, representing a valuable tool for the development of regional studies.